Analisis Implementasi dan Implikasi Hukum Pidana Zina dan Kohabitasi dalam KUHP Baru Indonesia terhadap Hak Asasi Manusia - Christian Dody Diori Marbun (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
Criminal law policy in Indonesia saw significant modifications with the adoption of the new Criminal Code (KUHP), particularly with regard to the regulation of cohabitation and adultery. Because it directly affects people's private life and may have an impact on human rights protection, this arrangement has sparked discussion in the community. This study intends to investigate the application of the penal provisions of adultery and cohabitation in the new penal Code and examine its consequences for the protection of human rights. The research method applied was normative legal research with a legislative, conceptual, and human rights approach. The study's findings show that the regulation and implementation of laws relating to adultery and promiscuity can lead to issues in law enforcement, particularly those relating to the right to privacy, the proportionality of punishment principle, and the potential for actual abuse of power. The conclusion of this study underlines the necessity for the judicial implementation of the law and geared towards the protection of human rights, as well as the examination of criminal law policies to be in line with the ideals of the rule of law, democracy, and respect for individual freedom.